Redesign of an electronics education curriculum - (:unkn) unknown (My University, 2002)
Department of Electronics and Computer Education Department of Technical Education Faculty of Marmara University educates students to become technical teachers for vocational and technical high schools and technologist for industry. Since its foundation in 1976 the curriculum of the department has been reviewed several times and some major changes have taken place. With the recent study on curriculum, modern approaches, techniques and tools are used and a structural process is initiated. These techniques are based on total quality management and continuous quality improvement studies.